PENGARUH PENERAPAN PENDEKATAN BRAIN BASED LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMAN 12 PADANG - Ade Silvia Yeni (Universitas Negeri Padang, 2014)
The one direction of learning process made students less participated in class. Less communication between teachers and students also made them affraid to conveyed their own opinion. This condition made the weaknesses of the students ability in thingking that impact on low marked of their result. One way to improve their result in learning was using Brain Based Learning approached which supposed to optimalize the worked of their brain, so that the learning process become meaningfull. The purpose of this study was to investigate the effect of applying the Brain Based Learning approach to the result of learning physics of class X in SMAN12 Padang. The type of research conducted by the quasi- experimental research design used is